"More human": Using ethnographic insights to develop a posthuman framework of 'extended recovery' for harmful drug use - Samuel Brookfield; Linda Selvey; Lisa Fitzgerald; Lisa Maher (Elsevier, 2023)
Background: The enduring conceptual confusion within drug use literature and research regarding the definition of addiction arises from the lack of reconciliation between two key concepts: (1) addiction occurs when someone loses control over their behaviour, and (2) recovery can only proceed when that individual chooses to regain control. This paper uses ethnographic insights to illustrate an alternative framework based on posthumanism and extended health that can resolve this tension: 'Extended Recovery'. Methods: Ethnographic fieldwork was conducted over eight months with 12 people engaging in methamphetamine recovery in Brisbane, Australia. Thematic analysis was conducted on transcripts and field notes. Results: Two exemplar case studies are discussed which demonstrate the interactive ecology of families, social networks, economic circumstances, legal proceedings, health and support services, and social capital from which drug use and recovery symbiotically emerged. Conclusion: Extended Recovery critiques the distinction between internal and external factors shaping the recovery of a central, self-authoring subject. Four recommendations are provided to guide policy and interventions that would align with this framework. (1) Policymakers should approach harmful drug use as a multi-dimensional health issue, treating health and illness as distributed and emergent. (2) Services should support models of care that emphasise family and social networks, rather than only individuals or populations. (3) Treatment services should be responsive to the divergent priorities of people using drugs, and the chronic nature of drug related harm. (4) Models of care should validate the forms of change and growth people can experience without being abstinent from drugs.